SOCIO-POLITICAL VIEWS OF JADIDISM REPRESENTATIVES - Muhiddinov Sardarkhan; Mustafayev J.Sh. (Лучшие интеллектуальные исследования, 2024)
Abstract: Liberating Turkestan from medieval backwardness and religious prejudice, reforming Sharia, spreading enlightenment to the people, the struggle to establish an autonomous government in Turkestan, freedom by establishing a constitutional monarchy and parliament in Bukhara and Khiva, and later a democratic republic system. and building a prosperous society, introducing a stable national currency and building a national army.